Graduate employability and higher education : past, present and future. - Bennett, Dawn (HERDSA Review of Higher Education v.5 p.31-61, 2018)
The question of how to prepare higher education students for employment is at the forefront of higher education, yet in many respects it is the wrong question. This review article poses an alternative question: how might we prepare higher education students to navigate an increasingly complex world and labour market in which they will need to think for a living? I begin by considering the labour market environment into which graduates transition. I align this with contemporary definitions of employability before revisiting my employability and related research undertaken over the past 20 years. In voicing possible solutions, I structure the article's latter sections according to the four challenges posed by the Australian Deputy Vice-Chancellors for response in the 2019 HERD Review: namely, university funding; commitment to change by university staff; dealing with complexity; and building capacity. [Author abstract]